AR/VR technologies in management and education - A. I. Sosnilo; M. Y. Kreer; V. V. Petrova (Управление)
The potential of some technological innovations for a long period of time remains either not fully explored or underestimated. The article gives a brief description of the AR and VR technologies, shows the possibilities of their use in various sectors and industries of the modern world economy. The paper provides an overview of the positive aspects and competitive advantages that AR and VR technologies can bring to companies engaged in the development and production of devices and instruments that allow using these technologies. This is a growth in sales of products and services, a reduction in operating costs, an increase in customer satisfaction, an improvement in the quality of product, services and service. The study also considers the limitations of using AR and VR technologies in educational environments. According to the authors, there are more industries and areas where AR and VR technologies can be applied.The paper analyses the volume of investments in the field of VR / AR, gives the forecasts of possible improvements of VR and AR devices, leading to creating of wider opportunities for their utilization in industrial, financial and educational spheres. The article presents the most successful examples of the implementation of AR and VR technologies in 2012-2021 in foreign and Russian companies. For statistical confirmation of the obtained results the authors performed a correlation analysis of the forecast estimates of the development of AR and VR technologies in 2021–2023. The paper makes the forecast of sales of technologies and devices in some sectors of the economy by 2024. Based on the analysis, the study concludes that there is a significant relationship between the electronics market as a whole and the VR/AR market.